The cinematic approach to the daily reality in the movie “Omar Gatlatou Al Rajla”: The founding of “the Algerian realist cinema” - Elmahmoudi, Tarek (Journal of Humanities & Social Sciences, 2022)
In the course of the eighties of the last century, Algerian cinema launched another tendency that concentrated on the Algerian actuality after independence and was labeled the "new cinema". The contents of this cinema were somewhat far from the authority of the “exaggerations” of liberation war which bounded the creative horizon and restrained every intellectual motivation and research act, and thus contributed to retaining cinema away from its factual role, particularly at this stage in the history of Algeria. This cinema trend scrutinized the social and economic circumstances within Algerian society during this period, and as result disturbing the notion of exaltation, stylized bravery, and the holiness of platforms. This was signified by moving towards deeper and more thoughtful visions related mainly to the modest citizen and his daily life, thus announcing the perpetuation of the transformation in Algerian cinema that began in the late seventies. This phase was established on solid basics. Fundamentally, the rise of a generation of young filmmakers who received academic training in numerous specialized European universities and who on their return to their homeland passed their dreams and mainly their new ideas which were built on audaciousness and innovation. Simultaneously with the new realism in Italy and the new trend in France, this enlightened vision was formed within Algerian cinema, and produced for the viewer a group of films that, although with a combining coordination, presented different and taboo liberated managements. In this esteem, the feature film “Omar Qatlatou Al Rajla” directed by Merzak Allouache is measured as the most significant title of the Algerian realist cinema, which deals with the social phenomena within the Algerian society, according to artistic and artistic methods that allow the development of the spectator’s sense of taste and enhance his knowledgeable and cinematic culture.